Chlorophyll-a Consentration in Parit Belanda River, Rumbai Pesisir District, Pekanbaru, Riau - Julianti '; Madju Siagian; Asmika H Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Anthropogenic activities conducted around the Parit Belanda River may produce organic pollutant that affect the water quality in general and it is reflected in the concentration of chlorophyll-a in the water. A research aim to determine the trophic status of the Parit Belanda River based on chlorophyll-a concentration has been carried out in December 2016. There are three stations namely station 1 (in the upstream), station 2 (in the middle), and station 3 (in the downstream). Samplings were conducted once/week for 4 weeks period. Water quality parameters measured were temperature, pH, transparency, turbidity, DO, CO2, nitrate and phosphate. Result shown that chlorophyll-a concentration range from 8.15-11.56 μg/L. Water quality parameters were as follows: temperature 28-290C, pH 5-6, transparency 46.5-55.8 cm, turbidity 19.24-25.06 FTU, DO 2.30-5.10 mg/L, CO2 32.96-54.94 mg/L, nitrate 0.076-0.137 mg/L and phosphate 0.221-0.264 mg/L. Based on the chlorophyll-a concentration, the Parit Belanda River can be categorized as mesotrophic.Keywords : chlorophyll-a, mesotrophic, water quality, Parit Belanda River